2017
DOI: 10.1155/2017/5087145
|View full text |Cite
|
Sign up to set email alerts
|

Massage and Storytelling Reduce Aggression and Improve Academic Performance in Children Attending Elementary School

Abstract: Background Aggressive behaviors must be addressed in elementary schools. Massage and storytelling can be strategies to deal with aggression because both involve experience exchange and social interaction. Both can decrease stress and anxiety and increase self-esteem. Objective To evaluate the effect of two interventions (massage and storytelling) on aggressive behaviors and academic performance of elementary school children. Method Three groups (n = 35 children in each group) of the second grade participated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
(43 reference statements)
3
6
0
Order By: Relevance
“…Some of the present findings are in line with the findings of (Roshan Chesli, 2012), (Gonçalves et al, 2017), (Nasirzadeh & Roshan, 2010), (Patel & Patel, 2017) and Burgess (2006). These studies generally indicate that enhancing social skills and establishing suitable interactions are the most important strategies for correcting the behavior of children with behavioral-emotional disorders.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Some of the present findings are in line with the findings of (Roshan Chesli, 2012), (Gonçalves et al, 2017), (Nasirzadeh & Roshan, 2010), (Patel & Patel, 2017) and Burgess (2006). These studies generally indicate that enhancing social skills and establishing suitable interactions are the most important strategies for correcting the behavior of children with behavioral-emotional disorders.…”
Section: Discussionsupporting
confidence: 90%
“…Some results of this study are consistent with the findings of Teglasi and Rothman (2001) who found that storytelling served as a beneficial technique to reduce students' communicational and social problems in classrooms. Some findings are also in line with the findings of Gonçalves et al (2017), who concluded that stories helped a narrator establish an emotional bond with listeners. This experience can reduce aggressive behavior in children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a similar paradigm used by another group of researchers, three groups of second grade children including massage, storytelling and control groups were compared on their aggressive behavior and academic performance after ten fifty-minute sessions [32]. In this case, both the massage and storytelling groups showed decreased aggressive behavior and improved academic performance, suggesting that giving children extra attention in itself helps reduce their aggression.…”
Section: Child and Adolescent Massage Therapymentioning
confidence: 99%
“…They can provide information on various conditions, conduct/interpret reports, improve communication between healthcare and education professionals and assist in the access to health resources. They can also provide education professionals information on interventions for children with disabilities 5,6 . In addition, it is essential to focus on the interests/questions of educators to structure more effective programs 7 .…”
mentioning
confidence: 99%